Pemasaran Minyak Kelapa Sawit (Crude Palm Oil) Menggunakan Strategi Analisis Swot Di PT. Perkebunan Nusantara III (Persero) Medan - Fuady Harahap, Iffan; Harahap, Syamsuddin; Sitinjak, Lentina; Maulia, Era; Ramut, Anuar (Universitas Katolik Santo Thomas Medan, 2025)
The agricultural sector in Indonesia still has many opportunities and bright prospects that have not been explored. In the agribusiness system, agro-industry is one of the subsystems that together with other subsystems form agribusiness. Crude palm oil (CPO) is one of Indonesia's leading commodities that has a strategic role in the national economy, both as a source of foreign exchange and as a provider of employment. The purpose of this study was to determine the marketing strategy of the Crude Palm Oil (CPO) industry at PT Perkebunan Nusantara III (PERSERO) MEDAN using the survey method, data analysis was carried out using descriptive methods and SWOT analysis. The research results obtained describe the SO (Strengths-Opportunites) strategy, namely improving good quality in order to maintain consumer loyalty (S1, O1) and optimizing product suitability according to what consumers want in fostering good relationships (S2, O2). Empowerment of young human resources in providing the best service to consumers. and supporting infrastructure in maintaining good relations (S1, S4, O4). Utilizing a good product image in maintaining consumer loyalty as a great asset for the company (S3, O1, O4). The results of the SWOT analysis described using the SWOT diagram show that the company is in quadrant I which means that PT Perkebunan Nusantara III Medan has an aggressive strategy, namely the company must be able to develop existing strengths and increase and maintain existing opportunities